Informal Milk Sharing. Issue 2 (March 2016) - Spatz, Diane L.
Abstract : When the new mother is unable to breastfeed or provide milk for her own child, human milk must be accessed from another source. There are three options: pasteurized donor human milk from a non-profit milk bank governed by the Human Milk Banking Association of North America, pasteurized donor human milk from a for-profit company, or through informal milk sharing. Our breastfeeding expert, Dr. Spatz explains why families may opt to or need to access human milk informally and why nurses and healthcare providers must have knowledge of informal milk sharing.